Efficacy and economics of ground cover management as a conservation biological control strategy against Tetranychus urticae in clementine mandarin orchards - Aguilar-Fenollosa, Ernestina; Pascual-Ruiz, Sara; Hurtado-Ruiz, Mónica A.; Jaques, Josep A. (2017)
Conservation biological control by means of ground cover offers an interesting alternative to chemical control of the twospotted spider mite Tetranychus urticae Koch (Acari: Tetranychidae), a key pest of clementine mandarins. The aim of this study was to investigate whether this tactic could actually achieve significant reductions in crop losses caused by this pest. The three most common cover practices used in citrus in Spain were compared: wild cover, a cover of Festuca arundinacea Scherb. (Poaceae), and bare soil. The action threshold was more often exceeded in wild cover than in bare soil or F. arundinacea. When expenditures and revenues were balanced, the most favorable cover was F. arundinacea (between 44.4 and 74.5% cost reduction relative to the most expensive one). F. arundinacea as a cover crop is a conservation biological control strategy highly recommendable for clementine producers. Although its use did not reduce mite populations below the action threshold, the population decreases obtained made the adoption of this tactic a beneficial alternative both ecologically and economically. (C) 2011 Elsevier Ltd. All rights reserved.